The experience of living alone as an older woman in the UK during the Covid pandemic: an interpretative phenomenological analysis - Cat Forward; Hafiz T. A. Khan; Pauline Fox (BMC Public Health, 2023)
Abstract Background and objectives More people are living alone across the life course: in later life this can have implications for practical and psychosocial support. The Covid pandemic emphasised the importance of this when the UK government restricted movement outside of households to limit the spread of disease. This had important ramifications regarding social contact and practical support. The objectives of this study were to explore the experience of older women living alone during this time, with a focus on health and wellbeing. Research design and methods This study used an Interpretative Phenomenological approach. Semi-structured interviews were undertaken with seven women (aged 65 +), living alone in the UK. Interviews were carried out between May and October 2020. Interpretative Phenomenological Analysis was used to analyse the transcripts. Results Findings show that life course events shaped how living alone was experienced in later life. Convergences and divergences in lived experience were identified. Three superordinate themes emerged from the Interpretative Phenomenological Analysis: Productivity, Ownership, and Interconnectedness. Discussion and implications Findings highlight the importance of life course events in shaping the experience of later life. They also provide a better understanding of the lived experience of living alone as an older woman, increasing knowledge of this group and how living alone can affect health and wellbeing. Implications for research and practice are discussed, such as the importance of recognising the specific support needs for this group in later life, and the need for further knowledge about groups whose needs are not met by standard practice.